Grasses as Raw Material for Paper Making in India - Guha, S. R. D.; Sharma, Y. K. (Indian Forester, 1968)
This article deals with utilization of grasses as a paper making raw material. After discussing the essential factors to be considered for choosing a paper making raw material, the authors have traced the history or the introduction of sabai grass as a paper making raw material and described its use. They have then described the work done at the F.R.I., Dehra Dun, on use of other forest grasses for paper making.